Towards depersonalized abacavir therapy: chemical modification eliminates HLA-B*57 : 01-restricted CD8+ T-cell activation. (28th November 2015) - Naisbitt, Dean J.; Yang, Emma L.; Alhaidari, Mohammad; Berry, Neil G.; Lawrenson, Alexandre S.; Farrell, John; Martin, Philip; Strebel, Klaus; Owen, Andrew; Pye, Matthew; French, Neil S.; Clarke, Stephen E.; et al.
Abstract : Objective: Exposure to abacavir is associated with T-cell-mediated hypersensitivity reactions in individuals carrying human leukocyte antigen (HLA)-B * 57 : 01. To activate T cells, abacavir interacts directly with endogenous HLA-B * 57 : 01 and HLA-B * 57 : 01 expressed on the surface of antigen presenting cells. We have investigated whether chemical modification of abacavir can produce a molecule with antiviral activity that does not bind to HLA-B * 57 : 01 and activate T cells. Design: An interdisciplinary laboratory study using samples from human donors expressing HLA-B * 57 : 01. Researchers were blinded to the analogue structures and modelling data. Methods: Sixteen 6-amino substituted abacavir analogues were synthesized. Computational docking studies were completed to predict capacity for analogue binding within HLA-B * 57 : 01. Abacavir-responsive CD8 + clones were generated to study the association between HLA-B * 57 : 01 analogue binding and T-cell activation. Antiviral activity and the direct inhibitory effect of analogues on proliferation were assessed. Results: Major histocompatibility complex class I-restricted CD8 + clones proliferated and secreted IFNγ following abacavir binding to surface and endogenous HLA-B * 57 : 01. Several analogues retained antiviral activity and showed no overt inhibitory effect on proliferation, but displayed highly divergent antigen-driven T-cell responses. For example, abacavir and N -propyl abacavir were equally potent at activating clones, whereas the closely related analogues N -isopropyl and N -methyl isopropyl abacavir were devoid of T-cell activity. Docking abacavir analogues to HLA-B * 57 : 01 revealed a quantitative relationship between drug–protein binding and the T-cell response. Conclusion: These studies demonstrate that the unwanted T-cell activity of abacavir can be eliminated whilst maintaining the favourable antiviral profile. The in-silico model provides a tool to aid the design of safer antiviral agents that may not require a personalized medicines approach to therapy. Abstract : Supplemental Digital Content is available in the text